Exploring the role of swimming in enhancing diet-based weight loss programs for athletes - Hassan, Cherkaoui Sidi; Nezha, Mouane (Intelektual Pustaka Media Utama, 2025)
This study explores the synergistic effects of customized dietary strategies and aerobic exercise, specifically swimming, on achieving weight loss while preserving muscle mass in athletes. The research highlights the importance of a holistic approach to weight management, integrating personalized diet plans with tailored exercise regimens. The study segmented participants into two groups, one following a standard diet for weight maintenance and another adhering to a similar diet augmented by regular swimming sessions aimed at weight loss. Results indicate that the diet-plus-swimming group exhibited significantly greater reductions in weight and body mass index (BMI) compared to the diet-only group, suggesting that incorporating swimming enhances the effectiveness of dietary interventions. These findings emphasize the potential of combining physical activities such as swimming with dietary modifications to achieve optimal weight management outcomes, providing a comprehensive approach to athlete health management. The study also underscores the need for personalized strategies that consider individual characteristics and preferences to support sustainable weight loss and improved health outcomes.